2009
DOI: 10.1093/ejechocard/jep071
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricle three-dimensional echography in corrected tetralogy of fallot: accuracy and variability

Abstract: Three-dimensional echocardiography combined to semi-automated quantification software shows fair agreement with MRI for RV volumes and EF measurement in patients with repaired ToF and adequate intra- and interobserver variability. These results suggest applicability for serial follow-up of patients with right heart congenital disease. However, the accuracy of 3DE echo diminishes with larger RV volumes, in part due to current difficulty to include the entire RV in the imaged sector. Technical progress in transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Post-operative electrophysiological sequelae are infrequent if repair is done at a young age. Besides PR, echocardiography can help in assessing other factors that can complicate the course of repaired TF such as RV dysfunction, LV dysfunction, and Ao regurgitation [59][60][61][62][63][64]. Adult patients late after correction of T/F showed impaired right ventricular myocardial function (revealed by TDI echocardiography) and reduced maximal working capacity [60].…”
Section: Specific Echocardiographic and Clinical Aspectsmentioning
confidence: 99%
“…Post-operative electrophysiological sequelae are infrequent if repair is done at a young age. Besides PR, echocardiography can help in assessing other factors that can complicate the course of repaired TF such as RV dysfunction, LV dysfunction, and Ao regurgitation [59][60][61][62][63][64]. Adult patients late after correction of T/F showed impaired right ventricular myocardial function (revealed by TDI echocardiography) and reduced maximal working capacity [60].…”
Section: Specific Echocardiographic and Clinical Aspectsmentioning
confidence: 99%
“…24,25 In clinical studies, however, it has often been reported that 3DE underestimates RV volumes and ejection fraction (EF) 26-28 compared with MRI. These were relatively small studies, and there have been some contradictory reports that showed nonsignificant bias 9,10,[29][30][31][32][33][34][35] or overestimation 15,[36][37][38][39] in some of the values, creating a major discrepancy in this field. To date, there has been no systematic attempt to synthesize the current data on the existence, extent, and factors of the bias.…”
mentioning
confidence: 99%
“…Another approach is to utilize information from orthogonal views to assist in delineating the endocardium, e.g., by tracing the short axis contours with guidance from one or two long axis views [23]. A limitation of current matrix array transducers is that the sector width does not allow imaging of the RV in its entirety in a significant proportion of adult patients within the single apical scan that is most commonly employed to acquire the image data [24]. This disadvantage is particularly present when the RV is enlarged, the very situation where quantification of RV function is important.…”
Section: Quantitation From Three-dimensional Echocardiographymentioning
confidence: 99%
“…Tomtec Imaging Systems (Unterschleissheim, Germany) markets a product that employs semiautomated analysis of volumetric 3D echo data sets ( Fig. 10.13); its accuracy and reproducibility have been extensively validated by comparison with MRI [17,18,20,24].…”
Section: D Analysis Of Multiple 2d Viewsmentioning
confidence: 99%